Molecular Cardiology Methods and Protocols - Sun, Zhongjie; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2005)
The application of molecular technology to the heart opens a new and promising avenue for both the study and cure of heart diseases that were once thought to be incurable. In Molecular Cardiology: Methods and Protocols, leading cardiac researchers from around the world describe in detail their own proven, cutting-edge techniques for gene therapy and stem cell therapy for heart diseases. The authors provide readily reproducible methods for genetic dissection, signal transduction, and microarray analysis. The protocols include techniques for gene transfer to heart tissue using viral and nonviral vectors, the basis for gene therapy of heart diseases, and for producing transgenic models of heart diseases, the novel and powerful tools for the study of heart disease pathogenesis. Many of the protocols employ not only molecular and cell biology techniques, but also in vivo approaches to myocardial repair using different types of stem cells, and include methods for expansion, purification, and genetic modification of stem cells. The protocols offer step-by-step laboratory instructions, an introduction outlining the principle behind the technique, and tips on troubleshooting and avoiding known pitfalls. Authoritative and highly practical, Molecular Cardiology: Methods and Protocols offers basic and clinical researchers the first major collection of the state-of-the-art molecular and cell biology techniques for the study and treatment of genetic and acquired heart diseases.
to Methods in Molecular Cardiology -- Gene Transfer and Gene Therapy for Cardiovascular Disease -- Gene Therapy Approaches to Cardiovascular Disease -- Gene Therapy for Myocardial Ischemia Using the Hypoxia-Inducible Double Plasmid System -- Cardiac Gene Delivery Using DNA–Adenoviral Constructs -- Manipulation of Neuronal Nitric Oxide Synthase Within the Paraventricular Nucleus Using Adenovirus and Antisense Technology -- TAT-Mediated Protein Transduction -- Expression of Human eNOS in Cardiac and Endothelial Cells -- Strategies of Conditional Gene Expression in Myocardium -- Gene Silencing Using Adenoviral RNAi Vector in Vascular Smooth Muscule Cells and Cardiomyocytes -- Stem Cell Therapy for Cardiovascular Disease -- Cardiac Commitment of Embryonic Stem Cells for Myocardial Repair -- Autologous Mesenchymal Stem Cells for Post-Ischemic Myocardial Repair -- Cellular Therapy With Autologous Skeletal Myoblasts for Ischemic Heart Disease and Heart Failure -- Protocols for Myocardial Infarction Repair Using Fetal Cardiac Myocytes -- Methods for Examining Stem Cells in Post-Ischemic and Transplanted Hearts -- Endothelial Progenitor Cell Culture and Gene Transfer -- Gene Analysis in the Injured and Hypertrophied Heart -- Delineation of Sequences Essential for Specific Promoter Activation During Pressure Overloaded Hypertrophy or Factor-Induced Hypertrophy -- Evaluation of the Cardiac Isoform of ?2-Macroglobulin as a Factor Inducing Cardiac Hypertrophy -- Detection of Apoptosis in Cardiovascular Diseases -- Detection of Cardiac Signaling in the Injured and Hypertrophied Heart -- Affymetrix Oligonucleotide Analysis of Gene Expression in the Injured Heart -- Identification and Validation of Loci and Candidate Genes Linked to Cardiac Hypertrophy -- Induction and Analysis of Cardiac Hypertrophy in Transgenic Animal Models -- Methods for the Detection of Altered ?-Adrenergic Receptor Signaling Pathways in Hypertrophied Hearts -- Transgenes in Cardiovascular Research -- Transgenic Mouse Models for Cardiac Dysfunction by a Specific Gene Manipulation -- Cardiomyocyte Defects in Diabetic Models and Protection With Cardiac-Targeted Transgenes -- Cardiac-Specific Overexpression of Angiotensin II Type 1 Receptor in Transgenic Rats.
Keywords: Cardiology; Cardiology